2022
DOI: 10.1002/chem.202202373
|View full text |Cite
|
Sign up to set email alerts
|

Organophotocatalytic [2+2] Cycloaddition of Electron‐Deficient Styrenes**

Abstract: A visible‐light organophotocatalytic [2+2] cycloaddition of electron‐deficient styrenes is described. Photocatalytic [2+2] cycloadditions are typically performed with electron‐rich styrene derivatives or α,β‐unsaturated carbonyl compounds, and with transition‐metal‐based catalysts. We have discovered that an organic cyanoarene photocatalyst is able to deliver high‐value cyclobutane products bearing electron‐deficient aryl substituents in good yields. A range of electron‐deficient substituents are tolerated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The [2+2] cycloaddition of trans ‐chalcone was selected for this initial validation. The cyclobutane motif is notable in a number of natural products and can be readily accessed via the [2+2] cycloaddition of a wide range of alkene substrates, including derivatised chalcones, cinnamates, cinnamamides, and styrenes, [40–43] promoted by either direct photoexcitation or by energy transfer photocatalysis. The cross‐cycloaddition of such substrates is also possible, in addition to the classical symmetric cycloaddition [43–44] .…”
Section: Resultsmentioning
confidence: 99%
“…The [2+2] cycloaddition of trans ‐chalcone was selected for this initial validation. The cyclobutane motif is notable in a number of natural products and can be readily accessed via the [2+2] cycloaddition of a wide range of alkene substrates, including derivatised chalcones, cinnamates, cinnamamides, and styrenes, [40–43] promoted by either direct photoexcitation or by energy transfer photocatalysis. The cross‐cycloaddition of such substrates is also possible, in addition to the classical symmetric cycloaddition [43–44] .…”
Section: Resultsmentioning
confidence: 99%
“…We observe the head‐to‐tail regioisomer exclusively, which indicates a triplet energy pathway rather than an electron transfer process as the latter would involve an unlikely primary radical intermediate. This reasoning has previously been used to exclude electron transfer in [2+2] photocycloadditions [3,36] …”
Section: Resultsmentioning
confidence: 99%
“…This reasoning has previously been used to exclude electron transfer in [2 + 2] photocycloadditions. [3,36] Recently 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP) was shown to reduce the triplet energy of quinolines by formation of hydrogen bonds. [37] In line with these observations, we hypothesized a similar case of solvent activation where water molecules form hydrogen bonds with the substrates in the Stern layer resulting in lowering of the triplet energy (Figure 3).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The byproduct 4 (4% yield), which was probably generated from the addition of the α-aminoalkyl radical to alkene, was also observed in this reaction . Control experiments indicated that photocatalyst, visible light, and reductant were all essential for this reaction, and the [2 + 2] cyclization byproduct 5 was achieved in 9% yield with 2.6:1 dr when i Pr 2 NEt was removed (entries 2 and 3). Notably, H 2 O had a significant impact on the reaction efficiency as only 22% of the desired product was detected in its absence, which may be due to water being the proton source (vide infra) (entry 4).…”
mentioning
confidence: 91%